Reversible Electrochromic Pattern in 3D Photonic Crystals Film from Thiol‐Acrylate‐Based Polymer‐Stabilized Blue Phase Liquid Crystals. Issue 7 (31st January 2023) - Wang, Meng; Song, He; Li, Xiaosong; Li, Zhaozhong; Li, Hui; Sun, Jian; Hu, Wei; Yang, Huai
Abstract: Endowing advanced 3D photonic nanoarchitectures with dynamic controllability is currently in the spotlight of soft‐matter photonics research. Herein, a well‐defined photopatterned polymer‐stabilized blue phase (PSBP) film with 3D electrically tunable photonic bandgap is fabricated by a liquid crystalline thiol–acrylate monomers system. Remarkably, the addition of thiol monomers can effectively improve the electrical tuning performance of the PSBP film and maintain excellent thermal stability simultaneously. The proportions of acrylate and thiol monomers are proved to be a key factor on the morphology structure of the polymer network in the PSBP system. By masked UV photopolymerization, a patterned sample with a high‐quality image and reversible nonsynergistic electrochromism is obtained. With increasing electric field, the patterned region changes from initial green reflection color to a red one, while no obvious visual color change occurs for the shading region with initial blue reflection color. The distinct electrically responsive behaviors are mainly caused by the microstructural difference of polymer networks, which is engendered by the migration of polymerizable monomers during polymerization. The research disclosed herein may provide new insights into the development of patterned 3D self‐assembled liquid crystalline photonic crystal toward anticounterfeiting, displays, colorimetric sensors, labeling technology, and programming photonics. Abstract : A well‐defined photopatterned polymer‐stabilized blue phase film with self‐organized 3D photonic bandgap is fabricated by using two types of liquid crystalline polymerizable monomers—acrylate and thiol. It exhibits reversible nonsynergistic shift of the photonic bandgap under electric field and visually shows an electrogenic redshift color change in the patterned area.